Reduce waiting times in a hospital emergency department using simulation - Medina León, Silvia (2010)
A discrete simulation model was developed for the obstetrics-gynecology emergency department of a regional public hospital. It was utilized the software Arena of Rockwell Automation to analyze the flow of patients, identify bottlenecks and propose improvements that reduce patient waiting times. The simulation model included from the patient arrival at the information module until the patient leaves the recuperation area in emergency. Scenarios evaluation was utilized to determine improvement proposals giving as result a 76% reduction of total waiting times.